IDENTIFICATION AND MANAGEMENT OF ALTERNARIAOCHROLEUCA–A CAUSE OF LEAF NECROSIS IN MONEY PLANT - S. Shafique; M. Rafique; N. Akhtar; S. Shafique (Journal of Animal and Plant Sciences, 2017)
Diseases caused by fungal pathogens are very common to occur worldwide. Biological control is a method that offers harmless fungal management program and an alternative for dependence on chemical treatments. A survey was conducted in vicinity of Institute of Agricultural Sciences, University of the Punjab, Lahore and Money plant (Epipremnum aureum) was found to be infected with fungal leaf spot. Infected samples were collected for isolation, purification, and identification of the pathogen. The identification was carried out for morphological characterization and genetically from nucleotide sequencing of amplified ITS1-5.8S-ITS4 region of rDNA. Alternaria ochroleuca was identified as a leaf spot causing pathogen of money plant. Afterwards, pathogenicity aptitude of identified pathogen was confirmed by re-isolation of same pathogen from the artificially innoculated leaves of host plant using detached leaf method. Further to this, biological control of A. ochroleuca was carried out using methanolic extract of Piper nigrum L. (Black pepper) and Amomum subulatum Roxb (Cardamom). Both types of extracts presented varied results. However, all the employed concentrations of methanolic Cardamom extract suppressed the fungal growth except 1.5% concentration. Contrastingly, Black pepper extract did not inhibit the fungal biomass production. Therefore, Cardamom extract was considered to be more effective in controlling A. ochroleuca growth. Further studies will be carried out to fractionate different compounds from Cardamom and to determine the efficacy of these compounds against target pathogen.
Keywords: Alternaria ochroleuca; Amomum subulatum; Biological control; Methanolic extract; Money plant; Piper nigrum